Analisis Ekonomi Sistem Tanam Padi Sawah di Kabupaten Konawe Sulawesi Tenggara - Zainal Abidin (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2013)
ABSTRACTEconomic Analysis of Several Models Rice Planting in Konawe Regency Southeast Sulawesi. Indonesian Agency Agricultural Research and Development (IAARD) has introduced some technology to enhance rice productivity, such as direct planting system and legowo model in transplanting system. Research was conducted to know agro economic performance of several models rice planting at Bendewuta Village Wonggeduku Subdistrict Konawe Regency, using 15 ha low land rice area by comparing three kinds of technology such as: (i) exsisting direct planting model (farmer technology), (ii) direct seeding legowo 2:1 model, and (iii) transplanting legowo 2:1 model. Each model was applied in 5 ha low land rice area at the same location. The result of research showed that the rice yield of legowo model (transplanting system and direct seeding) was higher 20.9% and 20.3% respectively than the rice yield of existing direct seeding planting model. Direct seeding legowo 2:1 model gave highest benefict, around IDR. 8,107,250/ha/season with BCR value 1.75. Changing technology from the existing direct seeding planting model to direct seeding planting legowo 2:1 model gave addition benefict around IDR.1,975,050 with MBCR value 6.96 and from transplanting legowo 2:1 model to direct seeding planting legowo 2:1 model add benefict IDR.425,100 with MBCR value 1.16. Direct seeding planting legowo 2:1 model has been adopted by farmer in several villages and was implemented around 100 ha only 1 season after this model was introduced in first season 2011. In the future, due to increasing planting cost of rice, direct seeding legowo 2:1 model could be can alternative way to decrease planting cost and to increase rice yield.. Key words: Economic analysis, planting system, rice ABSTRAK Badan Litbang Pertanian telah mengintroduksikan berbagai teknologi untuk meningkatkan produktivitas padi, antara lain sistem tanam benih langsung (Tabela) dan cara tanam legowo. Kajian sistem tanam padi dilakukan di Desa Bendewuta, Kecamatan Wonggeduku, Kabupaten Konawe pada luasan 15 ha dengan membandingkan tiga teknologi, yaitu (i) tabela biasa, (ii) tabela legowo 2:1 dan (iii) tapin legowo 2:1, yang masing-masing diaplikasikan pada 5 ha lahan sawah. Hasil pengkajian menunjukkan bahwa penanaman dengan sistem legowo baik dengan menggunakan tapin maupun tabela memberikan produktivitas lebih tinggi masing-masing 20,9% dan 20,3% dibandingkan dengan penggunaan tabela biasa. Sistem tabela legowo 2:1 memberikan keuntungan yang tertinggi yaitu Rp. 8.107.250/ ha dengan nilai BCR sebesar 1,75. Perubahan penerapan teknologi sistem tabela biasa menjadi sistem tabela legowo 2:1 memberikan tambahan keuntungan sebesar Rp.1.975.050 dengan nilai MBCR 6,96. Perubahan teknologi sistem tapin legowo 2:1 menjadi sistem tabela legowo 2:1 memberikan tambahan keuntungan sebesar Rp.425.100, dengan nilai MBCR 1,16. Penggunaan teknologi tabela legowo 2:1 telah direspon baik oleh petani di sekitar wilayah pengkajian, dimana pada MT II 2011 telah berkembang sekitar 100 ha yang menggunakan atabela model legowo 2:1. Ke depan, dengan makin meningkatnya biaya tanam, maka penanaman sistem tabela legowo 2:1 dapat menjadi salah satu alternatif bagi petani untuk mengurangi biaya tanam, dan meningkatkan produktivitas padi sawah. Kata kunci: Analisis ekonomi, cara tanam, padi sawah